Anemia in adolescents: does anemia in adolescents reduces the quality of the national generation? - Purwanti, Anik (BKM Public Health and Community Medicine, 2021)
Purpose: This paper reviewed the impact of anemia on adolescents and pregnant women on their babies. will the incidence of anemia affect the quality of the baby born? Content: Based on data from Riskesdas (2018), the prevalence of anemia, especially in pregnant women, increased from 37.1% (2013) to 48.9% in 2018. Meanwhile, the regulation in dealing with this problem was made in 2014, namely Permenkes No. 88/2014 on giving tablets add blood to women of childbearing age and pregnant women. Based on data from the Ministry of Health (2020), anemia in pregnant women can result in the risk of giving birth to low birth weight (LBW) babies, stunting, complications during childbirth, suffering from non-communicable diseases such as diabetes and heart disease later in life. In addition, Sukmawati (2019) also revealed that mothers who give birth more than three times are at risk of experiencing bleeding complications which can be affected by anemia during pregnancy and the risk of recurrent bleeding in subsequent pregnancies due to decreased hemoglobin levels. Socio-economic factors are an important factor in the incidence of anemia in the community. Those with low socioeconomic status tend to ignore the impact of anemia on their future generations (Siahaan, 2012). Apart from socio-economic factors, education and the level of awareness of adolescent girls and pregnant women in several regions of Indonesia regarding the impact of anemia and the importance of preventing anemia to reduce the prevalence of stunting in children under five are still lacking so that the government is still difficult to achieve the success of a program (Martini, 2015). Conclusion: The key to preventing anemia in adolescents is government involvement and cross-sector cooperation as well as community capacity to implement it.